2015
DOI: 10.1007/s12192-015-0598-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple chaperonins in bacteria—novel functions and non-canonical behaviors

Abstract: Chaperonins are a class of molecular chaperones that assemble into a large double ring architecture with each ring constituting seven to nine subunits and enclosing a cavity for substrate encapsulation. The well-studied Escherichia coli chaperonin GroEL binds non-native substrates and encapsulates them in the cavity thereby sequestering the substrates from unfavorable conditions and allowing the substrates to fold. Using this mechanism, GroEL assists folding of about 10-15 % of cellular proteins. Surprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 184 publications
(233 reference statements)
1
33
0
Order By: Relevance
“…Although some mitochondria and bacteria also possess more than one chaperonin subunit, it is still a fascinating question why the chloroplast uniquely contains divergent Cpn60 α/β chaperonin subunits as well as Cpn10/20 co-chaperonin types (Kumar et al, 2015 ). Transcriptome and proteome studies in Arabidopisis indicated expression levels of chaperonin and co-chaperonin genes differ according to developmental stage (Weiss et al, 2009 ), which increases the complex potential of the chaperonin system for regulation on both transcriptional and post-translational levels.…”
Section: Chloroplast Chaperonin and Co-chaperonin Proteinsmentioning
confidence: 99%
“…Although some mitochondria and bacteria also possess more than one chaperonin subunit, it is still a fascinating question why the chloroplast uniquely contains divergent Cpn60 α/β chaperonin subunits as well as Cpn10/20 co-chaperonin types (Kumar et al, 2015 ). Transcriptome and proteome studies in Arabidopisis indicated expression levels of chaperonin and co-chaperonin genes differ according to developmental stage (Weiss et al, 2009 ), which increases the complex potential of the chaperonin system for regulation on both transcriptional and post-translational levels.…”
Section: Chloroplast Chaperonin and Co-chaperonin Proteinsmentioning
confidence: 99%
“…GroEL was recently described as a pathogen-associated molecular pattern (PAMP) that triggers PAMP-triggered immunity (PTI) in Arabidopsis (69). Finally, GroEL plays a significant role in the adherence and subsequent biofilm formation in many bacteria (70). PGPRs were previously described to use phase variation to avoid stimulation of the host's immune system (23,36).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis in the innate ethanol producer S. cerevisiae reviewed that HSP33 and HSP104 were up-regulated when their functional conformations. A recent study systematically analyzed the GroE dependent proteins in E. coli, and found that 57 proteins could not be active in their native host E. coli without a well-functioning GroE chaperone system [31,32]. Moreover, it has been demonstrated that the E. coli xylose isomerase and arabinose isomerase, both previously reported as being non-functional in yeast [33,34], can work well in S. cerevisiae via co-expression of E. coli GroE [35].…”
Section: Engineering Strain Tolerance Towards Organic Solventsmentioning
confidence: 99%
“…Unlike other proteins with highly specific targets, chaperones have a broad range of substrates. For instance, the bacterial HSP60 chaperone, GroEL and its co-chaperone, GroES, which together assemble the GroE complex, work on numerous proteins [29,31,32], and GroE increases E. coli tolerance towards heat shock extreme or sudden changes in temperature. Previous studies reported that the overexpression of prokaryotic GroE can alleviate the inhibitory effects of various end-products on engineered strains [27].…”
Section: Introductionmentioning
confidence: 99%